Contemporary human rights issues in Malaysia - Shuaib, Farid Sufian (Sweet & Maxwell Asia, 2012)
The Malaysian Federal Constitution provides for fundamental liberties. However, taking into account that the Constitution was proclaimed in the environment where there was communist insurgencies and a nascent pluralist society, the fundamental liberties were laden with exceptions including on security and public order. The challenge for the constitutional players in the 21st century is to read the Constitution with a deep respect for values held dear by the society in the past but at the same to bring the spirit of the constitution into accord with the present realities. The polemics and contested issues canvassed in following discussion will look at these tensions which involve traditions and understanding of the relationship between the State and the people.